Effects of thermal stimulation on neurons and astrocytes cultured from the rat median preoptic nucleus. Issue 17 (5th December 2018) - Leisengang, Stephan; Ott, Daniela; Gerstberger, Rüdiger; Rummel, Christoph; Roth, Joachim
Abstract : Warming or cooling of the median preoptic nucleus (MnPO) in-vivo evokes appropriate thermoregulatory responses. In the present study, we aimed to investigate whether single neurons (and astrocytes) of primary rat MnPO cell cultures maintain properties, which are consistent with their putative role within the central thermoregulatory structures. Using the fura-2 ratio imaging technique, we therefore measured changes of intracellular Ca 2+ concentrations ([Ca 2+ ]i ) in neurons of rat MnPO primary cultures stimulated by rapid cooling from 37 to 25°C, or warming from 37 to 45°C, or glutamate, the transmitter which transfers thermal information to MnPO neurons. In the first experiment, we tested the responses to external cooling in a group of 212 neurons. Overall, 165 of these neurons were responsive to stimulation with glutamate; just four of them responded to the cold-stimulus with an increase of [Ca 2+ ]i, and only one of these neurons was responsive to stimulation with menthol. In the second experiment, 24 of 327 neurons and 23 of 241 astrocytes responded to external warming with quick and pronounced Ca 2+ signals. Another 33 (10%) neurons showed a moderate and slowly developing increase of [Ca 2+ ]i during the warming, which reflected the temperature changes in the chamber. These data correspond to properties of MnPO neurons upon thermal stimulation obtained by other experimental approaches. Primary cultures derived from the rat MnPO can thus be used to investigate neuronal thermosensitive properties and their possible modulation by other stimuli.